Search for a heavy Higgs boson decaying into two lighter Higgs bosons in the ττbb final state at 13 TeV; Journal of High Energy Physics; Vol. 2021, iss. 11 - Tumasyan A. R.; Adam W. Wolfgang; Andrejkovic J. W. Aleksandr Dmitrievich; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2021, 2021)
Title screen